Effect of Dimple Size onto Wear Rate of Mild Steel AISI 1060 Surface - Mohd Rahimi, Ramli; Norasiah, Abd Razak; Izwan, Ismail; Ahmad Shahir, Jamaludin; Ahmad Rosli, Abdul Manaf (2021)
This paper presents the effect of the dimple size and dimple density on the wear properties of mild steel AISI 1060 surface under constant loading. The dimple surface texture is produced using a ball-end-nose milling tool on a cross-sectioned surface of 32.5 mm cylindrical sample with a CNC milling method. The samples acted as the pin for pin-on-disk apparatus with constant loading setup. The dimples size is between 1 mm to 4 mm. The wear size on samples are ana-lyzed using 3D laser confocal microscopy image analysis technique. The result shows that the highest wear rate occurred at the samples with the smallest dimple diameter of 1 mm, while no significant of wear observed on samples with the largest dimple size of 4mm. It is expected that dimple size has a significant effect onto the contact between pin and surface, as the effect of friction reduced with the reduction of contact size.